Effects of depression on the life of the main character in Her movie by Spike Jonze - Ni Luh Sintami; I Gusti Agung Sri Rwa Jayantini; I Wayan Juniartha (Universitas Islam Sultan Agung, 2022)
People are coping with various problems in life that may influence their mental health if they fail to manage them. One kind of mental illness is depression that is frequently marked by the feeling of helplessness, disliking oneself, and shame for being weak. Being aware of depression signs by learning from any kind of media including movie will help people to control their mental and emotional condition. This study attempts to find out the effects of depression on the main character in Her, a two-hour-five-minute movie that is said to be a romance narrative about the relationship between Theodore, a sensitive, depressed and lonely guy with his computer operating system (OS) called Samantha. This study applied a qualitative descriptive method that was realized through observation and content analysis technique. To reveal the psychological exploration focusing on Theodore’s depression, the obtained data were classified based on the relevant categories describing effects of depression. The results show that there are five effects of depression taking place on the life of the main character, Theodore, namely (1) self-blame (2) low self-esteem, (3) loss of appetite, (4) trouble concentrating and (5) trouble sleeping. These five effects are triggered by Theodore’s helplessness due to his divorce that he makes him difficult to move on and the surrounding environment that frequently mocks him.